2020
DOI: 10.1002/adfm.202002274
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Caged IrOx for Facile Preparation of “Six‐in‐One” Nanoagent for Subcutaneous and Lymphatic Tumors Inhibition against Recurrence and Metastasis

Abstract: Single nanocarriers with intrinsic characteristics of diagnosis, effective therapy against solid malignancies with fatal metastasis, and tumor microenvironment regulation are promising in construction of a simple and effective multimode nanotheranostic system. Herein, multi‐caged IrOx nanocarriers are fabricated by direct thermal hydrolysis strategy, which exhibit good sono‐photodynamic response, outstanding gemstone spectral computed tomography, and photoacoustic (PA) imaging capabilities, universal loading, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Both Ce6 and IrO 2 have been reported to generate singlet oxygen ( 1 O 2 ) under US stimulation. [38,39] We measured the SDT performance of HC, HIr, and HCIr with DPBF, which was the 1 O 2 probe (Figure 2h). After 10 min of US stimulation (1.0 W cm −2 , 1.0 MHz, 50% duty cycle), the absorbance of DPBF in the HC solution dropped to 63.9% at 410 nm, and it dropped to 76.4% in the HIr solution, and in the HCIr solution it dropped to 45.7%, while the absorbance of the PBS group did not change significantly.…”
Section: In Vitro Sdt Effects and Gsh Depletion Ability Of Hcir Nanoc...mentioning
confidence: 99%
“…Both Ce6 and IrO 2 have been reported to generate singlet oxygen ( 1 O 2 ) under US stimulation. [38,39] We measured the SDT performance of HC, HIr, and HCIr with DPBF, which was the 1 O 2 probe (Figure 2h). After 10 min of US stimulation (1.0 W cm −2 , 1.0 MHz, 50% duty cycle), the absorbance of DPBF in the HC solution dropped to 63.9% at 410 nm, and it dropped to 76.4% in the HIr solution, and in the HCIr solution it dropped to 45.7%, while the absorbance of the PBS group did not change significantly.…”
Section: In Vitro Sdt Effects and Gsh Depletion Ability Of Hcir Nanoc...mentioning
confidence: 99%
“…Because of the ultrasmall size and the high dispersion of the Ir NCs inside BOD-Ir NCs, no characteristic peaks of Ir were detected in its XRD pattern (Figure S2). 33,34 XPS showed characteristic peaks of Ir−N (399.3 eV) and Ir−O (531.0 eV) (Figure 1e). 35,36 Considering that BOD is the only source of N and O in the reaction system, it can be concluded that BOD formed chemical bonds with the Ir NCs, which were highly helpful in stabilizing Ir NCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Very recently, Zhen et al developed a "six-in-one" nanoplatform for multimodal imaging-guided and O 2 enhanced SDT/PDT/chemotherapy synergetic cancer therapy (Figure 22). [138] The multicaged IrO x nanocarriers were first fabricated using a thermal hydrolysis strategy. The group further demonstrated the catalase-like, PDT, and SDT activity of IrO x .…”
Section: Trimodal Synergistic Therapy Based On Sonodynamic Therapymentioning
confidence: 99%